Assessment of Oil Palm Fresh Fruit Bunches Harvesters Working Postures Using Reba - Mohd Nawi, Nur Syazwani; Md Deros, Baba; Nordin, Norani (Trans Tech Publications Ltd, 2013)
Ergonomics has plays an important role to improve occupational health and work productivity in most industries in Malaysia including agriculture. However, most of the workers in Malaysia especially in oil palm plantation do not highlight ergonomics awareness as priority for their safety and health. They still using manual tools and consequently exposed to ergonomics risk factors. The objective of this study is to evaluate working postures during harvesting oil palm fresh fruit bunches. The Rapid Entire Body Assessment (REBA) is used to evaluate risks working postures and movements corresponding to the tasks. From the analysis, it is revealed that most of the oil palm workers were affected by musculoskeletal disorders especially on left and right hand side. Immediate action such as conduct ergonomics training for the workers must be taken to solve this ergonomic problem